Cured characteristics of non-nitrite-ham produced with Ocimum gratissimum as additive (International Journal of Agricultural Research, Innovation and Technology, 2023)
Cured meats are desirable to consumers across the world. Unfortunately, the use of nitrite to obtain cured characteristics has health implications for consumers. Three (3) kg each of ham were produced and labeled as H0, H1, H2, H3 and H4, respectively. H0 represented traditional ham produced with nitrite-curing salt and H4 contained common salt alone. H1, H2 and H3 were produced with 15.0 mg kg-1, 30.0 mg kg-1 and 60.0 mg kg-1 Ocimum gratissimum leaf extract as an additive with common salt. Proximate composition, pH, water activity and residual nitrite levels in treatments as well as color profiles were studied. The percentage contents of moisture, fat, protein and ash ranged from 40.02 (H3) to 41.20 (H4), 2.05 (H0) to 2.61 (H2), 19.37 (H4) to 20.83 (H3) and 2.27 (H4) to 2.69 (H2), respectively. Residual nitrite levels reduced significantly (P0.05) from nitrite-cured ham, but redness of common-salt cured ham was significantly lower (P>0.05) compared to 60.0 mg kg-1 Ocimum gratissimum-common-salt-cured and conventionally cured types of ham. It was concluded that Ocimum gratissimum leaf extract as an additive can potentially influence the development of desirable characteristics in ham.Int. J. Agril. Res. Innov. Tech. 12(2): 60-63, December 2022